Eksistensi Karya Seniman Minangkabau Syofyani Yusaf - Kemala Dwina Putri; Tati Narawati; Trianti Nugraheni (Gondang: Jurnal Seni dan Budaya, 2021)
This study intend to analyze the creations of Syofyani Yusaf dance. Study methods using the phenomenological method. Data collection techniques using questionnaires and interviews. The study subject is Syofyani Yusaf. Data analysis techniques using evaluative descriptive. Syofyani Yusaf is one of the prominent artist from West Sumatera. At present there are around 20 dances created. These dances have been studied through dance studio, formal school, and study programs in art colleges. The results of an analysis of Syofyani’s dance shows; (1)  the dances theme originaly come from the life of the Minang cultures; (2) Preservation of dance creations is carried out through culture exchange programs and culture knowledge. The results of the study can be concluded that dance creations by Sofyani Yusaf are sill performed and studied by the people not only from the Minang tribe but also another tribes. It is recommended that teachers in formal and non-formal schools become agents of culture exchange programs and culture knowledge.